PREVELANCE AND ASSOCIATED RISK FACTORS FOR PLANTAR FASCIITIS AMONG SECURITY FORCES PERSONNEL IN PESHAWAR - Ul Abidin, Syed Zain; Haneef, Kinza; Malik, Nida Rahim; Mashal, Maryyam; Haneef, Kinza; Zeb, Alam; Ur Rahman, Mujeeb (Annals of Allied Health Sciences, 2019)
OBJECTIVES: To find out the prevalence and factors related with plantar fasciitis in security force of Peshawar METHODS: Cross-sectional survey was conducted to find out the prevalence of plantar fasciitis in police force of Peshawar, Pakistan. We obtained our targeted sample of 364 was obtained from 12 police stations using convenience sampling. Data was analyzed through SPSS version 20. RESULT: The estimated occurrence of heel pain came out to be 10.6%. Among them the prevalence of plantar fasciitis was 13.2%. Age, obesity, foot wear, foot deformity, standing duty hours and the type of job were among the risk factors. CONCLUSION: The condition was found to have low prevalence. Age group 20-40, hard shoe wear, field-work and prolonged standing (more than eight hours) were found to have strong association with the condition.